2012
DOI: 10.1016/j.ijpe.2011.08.022
|View full text |Cite
|
Sign up to set email alerts
|

On the replenishment policy when the market demand information is lagged

Abstract: We consider a situation where the most up-to-date information on the market demand and the inventory levels is not available to a replenishment decision maker in a single echelon of a supply chain. The objective of the decision maker is to minimise the sum of the inventory and the production costs. An intuitively attractive strategy under this setting might be to reduce the information time lag as much as possible by utilising information technologies such as RFID. We call this strategy the Time lag Eliminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Lee et al (1997) and Chen et al Over the years others have further discovered that this relationship does not always hold when the demand is auto-correlated (Luong, 2007). As for the information delay, some authors have found that delayed demand information reduces the bullwhip effect and 'can sometimes be good news for upstream suppliers' (Miyaoka & Hausman, 2004;Zhang, 2005;Hosoda & Disney, 2012). …”
Section: Elements In Bullwhip Modellingmentioning
confidence: 99%
“…Lee et al (1997) and Chen et al Over the years others have further discovered that this relationship does not always hold when the demand is auto-correlated (Luong, 2007). As for the information delay, some authors have found that delayed demand information reduces the bullwhip effect and 'can sometimes be good news for upstream suppliers' (Miyaoka & Hausman, 2004;Zhang, 2005;Hosoda & Disney, 2012). …”
Section: Elements In Bullwhip Modellingmentioning
confidence: 99%
“…Analogously, two studies agree on the fact that demand delays increase (3) Impact on inventory variability: the work of Lu et al [52] provides some insights on the impact of demand error on inventory variability, which may increase or decrease depending on the demand shock, on information reliability and if errors occur during or before the replenishment. Moreover, four studies [18,19,35,42] show that demand delays increase inventory variability.…”
Section: Complexitymentioning
confidence: 99%
“…A bad synchronization leads to delayed information regarding market sales and/or inventory levels (i.e., the information transmitted upstream is received one or more periods later). The impact of such information delays on SC performance remains unclear in the literature; for example, Hoberg and Thonemann [17] state that the presence of unsynchronized processes or inadequate communication structures hinders the widespread availability of real-time information, thus harming the overall SC performance; Hosoda and Disney [18,19] show that while the first level of a SC can benefit from shorter time delays, the benefit perceived by the second level of the SC is minor or even detrimental.…”
Section: Introductionmentioning
confidence: 99%
“…The value of + is known to the manufacturer, since all information is local. Hosoda and Disney (2012) showed that in a traditional supply chain setting, regardless of the ordering policy used,…”
Section: The Ordering Policymentioning
confidence: 99%